Strategies based on nido-carborane embedded indole fluorescent polymers: their synthesis, spectral properties and cell imaging studies - Wang, Lei; Mao, Lingwei; Feng, Xibing; Wang, Shuo; Jin, Guofan (Frontiers in Chemistry, 2024)
The continuous preparation scheme EPO-Poly-indol-nido-carborane (E-P-INDOLCAB), L100-55-Poly-indol-nido-carborane (L-P-INDOLCAB), RS-Poly-indol-nido-carborane (S-P-INDOLCAB), and RL-Poly-indol-nido-carborane (R-P-INDOLCAB) were used to prepare the four types of acrylic resin-coated nido-carborane indole fluorescent polymers. After testing their spectral properties and the fluorescence stability curve trend at various acidic pH values (3.4 and 5.5, respectively), L-P-INDOLCAB and S-P-INDOLCAB were determined to be the best polymers. The stable states of the two polymers and the dispersion of the nanoparticles on the system’s surface during Atomic Force Microscope (AFM) test are shown by the zeta potentials of −23 and −42 mV. The dispersion of nanoparticles on the system’s surface and the stable condition of the two polymers were examined using zeta potential and atomic force microscopy (AFM). Transmission electron microscopy (TEM) can also confirm these findings, showing that the acrylic resin securely encases the interior to form an eyeball. Both polymers’ biocompatibility with HELA cells was enhanced in cell imaging, closely enclosing the target cells. The two complexes displayed strong inhibitory effects on PC-3 and HeLa cells when the concentration was 20 ug/mL, as validated by subsequent cell proliferation toxicity studies.